Azohydromonas caseinilytica sp. nov., a Nitrogen-Fixing Bacterium Isolated From Forest Soil by Using Optimized Culture Method - Dahal, Ram Hari; Chaudhary, Dhiraj Kumar; Kim, Dong-Uk; Kim, Jaisoo (Frontiers in Microbiology, 2021)
A bacterial strain designated strain G-1-1-14T was isolated from Kyonggi University forest soil during a study of previously uncultured bacterium. Cells of strain G-1-1-14T were motile by means of peritrichous flagella, Gram-stain-negative, rod-shaped, able to grow autotrophically with hydrogen and fix nitrogen. Phylogenetic analysis based on 16S rRNA gene sequence indicated that strain G-1-1-14T belonged to the genus Azohydromonas. The closest species of strain G-1-1-14T were Azohydromonas ureilytica UCM-80T (98.4% sequence similarity), Azohydromonas lata IAM 12599T (97.5%), Azohydromonas riparia UCM-11T (97.1%) and Azohydromonas australica IAM 12664T (97.0%). The genome of strain G-1-1-14T was 6,654,139 bp long with 5,865 protein-coding genes. The genome consisted N2-fixing genes (nifH) and various regulatory genes for CO2-fixation and H2 utilization. Principal respiratory quinone was ubiquinone-8 and major polar lipids were phosphatidylethanolamine, diphosphatidylglycerol and phosphatidylglycerol. The major fatty acids were summed feature 3 (iso-C15:0 2-OH and/or C16:17c), C16:0, summed feature 8 (C18:17c and/or C18:16c) and cyclo-C17:0. The DNA G+C content was 69.9%. The average nucleotide identity (OrthoANI), in silico DNA-DNA hybridization (dDDH) and conventional DDH relatedness values were below the species demarcation values for novel species. Based on genomic, genetic, phylogenetic, phenotypic and chemotaxonomic characterizations, strain G-1-1-14T represents a novel species within the genus Azohydromonas, for which the name Azohydromonas caseinilytica sp. nov. is proposed. The type strain is G-1-1-14T (=KACC 21615T = NBRC 114390T).